Negative Moderating Effect of Social Intelligence on the Relationship between Entrepreneurial Talent and Sustainable Performance among Technology-based SMEs in Malaysia - Dayang Hasliza, Muhd Yusuf (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2018)
Link to publisher's homepage at http://ijbt.unimap.edu.my